Partner robot using programmable logic control (PLC) - Mohammad, Mohd Mizwan (2005)
This main purpose of this project is to fulfill the requirement to complete the degree courses in Electrical Engineering. Its objective is to develop problem solving, analysis, synthesis and evaluation skills in the field of Electrical Engineering. The aim of this project is to implement the Partner Robot using Programmable Logic controller (PLC). The system designed is used to control the home appliances besides providing a good servant robot service at home. The program which controlled the system is written in ladder diagram. This program is entered to the PLC CPU using the window programming software called CX-Programmer. The other features of partner robot system such as proximity sensor that design to stop the robot immediately for safety first purpose, the wide range of Light Detector Resistance(LDR) gripper sensor that can grips the objects with special limit switch design to controls the pressure when gripping the glass and delicate well the objects. The robot also is design to stop and reset all the operation when the overflow current appears. The partner robot is operating in low dc voltage 24Vdc and the battery also can be charge and last longer more than normal battery. The used of PLC not only as a software control but with advancement in controller technology, it is also used as a drives, motion and process control with a single, integrated control system.